2021
DOI: 10.1002/prp2.839
|View full text |Cite
|
Sign up to set email alerts
|

TROIKA‐1: A double‐blind, randomized, parallel group, study aimed to demonstrate the equivalent pharmacokinetic profile of HD201, a potential biosimilar candidate to trastuzumab, versus EU‐Herceptin® and US‐Herceptin® in healthy male subjects

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The clinical demonstration of PK equivalence in healthy participants between HD201 and referent trastuzumab sourced from the US and European Union was established. 5 Additional PK assessment for patients who are receiving iterative cycles of trastuzumab is required and was part of the TROIKA study. 3 Assessment of C trough at cycles 5 and/or 8 established equivalence, which is relevant because a C trough value higher than the threshold of biological activity is the key PK parameter for consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical demonstration of PK equivalence in healthy participants between HD201 and referent trastuzumab sourced from the US and European Union was established. 5 Additional PK assessment for patients who are receiving iterative cycles of trastuzumab is required and was part of the TROIKA study. 3 Assessment of C trough at cycles 5 and/or 8 established equivalence, which is relevant because a C trough value higher than the threshold of biological activity is the key PK parameter for consideration.…”
Section: Discussionmentioning
confidence: 99%
“…During development, to justify the changes in the manufacturing process in addition to the previously reported phase I study in healthy participants, a second phase I study that demonstrated pharmacokinetic equivalence was conducted. 4,5 The aim of the present TROIKA study represents the ultimate step and is designed to show similar efficacy and safety between HD201 and referent trastuzumab in patients with ERBB2-positive early breast cancer. The primary objective was to demonstrate the equivalent clinical efficacy in terms of the total pathological complete response (tpCR) rate assessed at the time of surgery.…”
mentioning
confidence: 99%
“…Demarchi et al [ 61 ] also conducted a phase I study in healthy individuals to demonstrate pharmacokinetic equivalence. The main objective was to demonstrate the equivalence of HD201, EU-Herceptin ® , and US-Herceptin ® .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies, and these data support the continued development of the test drug as a biological drug candidate similar to the reference drug (Table S4). 11‐20 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies, and these data support the continued development of the test drug as a biological drug candidate similar to the reference drug (Table S4). [11][12][13][14][15][16][17][18][19][20] Immunogenicity analysis showed that all time points in the reference group and other time points in the test group were negative for ADA except for one weak positive case in the test group before administration. The results are similar to those of other biosimilar studies, suggesting that these two drugs have low immunogenicity (see Table S4).…”
Section: Discussionmentioning
confidence: 99%